Mechanically exfoliated In2Se3 as a saturable absorber for mode-locking a thulium-doped fluoride fiber laser operating in S-band - Ahmad, Harith; Reduan, Siti Aisyah; Ooi, Shok Ing; Ismail, Mohd Afiq (Optical Society of America, 2018)
The rise of 2D materials since the discovery of graphene has been exponential. Their mechanical, electrical and optical properties are exceptional, similar to their 3D counterparts. In this paper, an α − In2Se3 crystal is mechanically exfoliated and transferred directly onto a fiber ferrule to serve as a saturable absorber (SA). A thulium-doped fluoride fiber is used as a gain medium to generate mode-locked pulses together with the In2Se3-based SA. The SA has a modulation depth of 14.6% and a saturation intensity of 0.4 kW∕cm2. The passively generated mode-locked pulses have a repetition rate of 6.93 MHz and a pulse width of 5.79 ps. The mode-locked pulses also have a signal-to-noise ratio of 65.4 dB and a time-bandwidth product of 0.36. The pulse energy and peak power are 0.179 nJ and 27.2 W, respectively.